2012
DOI: 10.2500/aap.2012.33.3509
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of mometasone furoate nasal spray for nasal symptoms, quality of life, rhinitis-disturbed sleep, and nasal nitric oxide in patients with perennial allergic rhinitis

Abstract: Intranasal corticosteroid therapy has exhibited effectiveness for improving nasal symptoms and quality of life (QOL) scores associated with seasonal allergic rhinitis. We prospectively investigated the efficacy of mometasone furoate nasal spray (MFNS) for improving the total nasal symptom score, QOL score, and sleep quality in subjects with perennial allergic rhinitis (PAR). Nasal airway conditions were also objectively assessed by measuring nasal nitric oxide (NO). Fifty-seven patients with PAR were randomize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 0 publications
1
32
0
1
Order By: Relevance
“…On the other hand, a recent study of a cohort of adolescents demonstrated lower, albeit not significantly, nNO values in active smokers compared to non‐smokers . Table summarizes individual and environmental factors that may affect nNO values . Compared to velum closure techniques, tidal breathing results in significantly reduced nNO levels .…”
Section: Introductionmentioning
confidence: 97%
“…On the other hand, a recent study of a cohort of adolescents demonstrated lower, albeit not significantly, nNO values in active smokers compared to non‐smokers . Table summarizes individual and environmental factors that may affect nNO values . Compared to velum closure techniques, tidal breathing results in significantly reduced nNO levels .…”
Section: Introductionmentioning
confidence: 97%
“…We did not examine FFNS monotherapy in this study in consideration of the actual circumstances in Japan, where the prescription rate for INSs by GPs and the use of INSs in patients with pollinosis are both relatively low14,16. The addition of FFNS to LCTZ, however, demonstrated a significant suppression and delay in the development of nasal symptoms, compared with LCTZ monotherapy, in the present study, indirectly but clearly indicating the potent efficacy of FFNS.…”
Section: Discussionmentioning
confidence: 53%
“…In addition, an internet survey conducted by Konno and Kubo15 on the attitude of JC pollinosis patients toward drug adherence showed that 72% of the patients who were prescribed AHs ( n  = 8599) took the drug(s) regularly, just as prescribed, on the other hand only 38% of the patients who were prescribed INS ( n  = 4552) used the drug every day or frequently, while the remainder used the drug on demand. In this respect, INSs are not widely used in Japan because of the preferences of patients and a lack of understanding regarding their efficacy16. Therefore, the administration of second-generation AHs has been the mainstay of treatment for SAR, and the single use of INS presents difficulties, even if the patient’s symptoms are severe, in the present clinical setting in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…Symptom scores, nasal hyperreactivity and nasal volumes improved at the end of a 3-week treatment course [11]. Similarly, Yamada et al [12 ]have prospectively investigated the effectiveness of the mometasone furoate nasal spray in improving the total nasal symptom score, sleep quality and quality of life in subjects with PAR. Their results indicated that treatment with intranasal mometasone furoate improved nasal symptoms, upper airway condition, sleep quality and quality of life in Japanese PAR patients [12].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Yamada et al [12 ]have prospectively investigated the effectiveness of the mometasone furoate nasal spray in improving the total nasal symptom score, sleep quality and quality of life in subjects with PAR. Their results indicated that treatment with intranasal mometasone furoate improved nasal symptoms, upper airway condition, sleep quality and quality of life in Japanese PAR patients [12]. Meltzer et al [13 ]have suggested that the use of the mometasone furoate nasal spray improved nasal symptoms, sleepiness, and impairment in daily activities in PAR.…”
Section: Discussionmentioning
confidence: 99%